A post-training evaluation of a - van Steenderen, Margaret (My University, 2011)
The research problem was to evaluate a “Grow your Business” training course that had been run amongst informal traders. The City of Johannesburg rolled out the training course to 962 traders during 2005 and 2006. They contracted Wits Enterprise to write the programme and to roll out the facilitation. The programme ran over fourteen weeks, with a workshop once a week and was aimed at providing business skills to traders. The aim of this report is to see if the training is worthwhile running in similar environments. Kirkpatrick’s Levels for evaluating training was identified as a useful theoretical model to use to assist in the evaluation. The four levels are theorised to be interlinked and are reaction, learning, behaviour and organisational outcomes. The approach was to take the outcomes of the course and to test them using questions based on the various levels of Kirkpatrick’s model. This was done through the administration of questionnaires, with a final count of 85 being used. The overall findings for the course have been positive, with traders recommending the course for others and overall showing positive responses. After evaluation of the data it is recommended that this course be run in similar settings.
MBA - WBS
Keywords: Informal traders; Business courses